Considering lactate dehydrogenase (LDH) concentration in nasal-wash (NW) as a marker in evaluating the outcome of patients with bronchiolitis - M., Barak; M., Mirzarahimi; F., Amani; Y., Ghaemian; Ahadi, Adel (International Journal of Research in Medical Sciences, 2017)
Background: Estimation of bronchiolitis severity in infants is still an important issue and there are no standard methods to help physicians for better evaluation and management of clinical status of these patients. The aim of this study was to investigate the role LDH concentration in NW as a biomarker in evaluation the outcome of patients suffering bronchiolitis in Bu Ali Hospital, Ardabil. Methods: 100 children with bronchiolitis aged below 2 years entered the study. Nasal wash sample was extracted from all patients using 2 ml of normal saline. Samples were sent to laboratory to measure LDH level. Data were analyzed by statistical methods in SPSS.16. Results: The mean age of patients was 6.9±3.7 months and 57% of them were male. 42% of patients had mild bronchiolitis and 58% of them suffered from severe bronchiolitis. The LDH level of nasal wash fluid was neither related with gender nor with age. But it was significantly lower in patients who required oxygen therapy and had fever compared with those who did not require oxygen therapy and without fever. Moreover, LDH level showed a significant negative association with hospital stay (r= -0.570, p<0.001) and bronchiolitis severity (r= -0.440, p<0.001) in a way that its concentration was significantly lower in patients with hospital stay longer than 24 hours compared with hospital stay shorter than 24 hours, and in patients with severe bronchiolitis compared with mild bronchiolitis. Conclusions: According to results of this study, LDH measurement in nasal wash fluid can be used as a biochemical marker to evaluate clinical outcomes of bronchiolitis in children younger than 24 months.